'I'll take two.' Migration, terrorism, and the Italian military engagement in Niger and Libya. Issue 2 (14th March 2020) - Ceccorulli, Michela; Coticchia, Fabrizio
ABSTRACT: In January 2018, the Italian parliament approved a new military operation in Niger and an extension to the existing deployment in Libya. Italian leaders explicitly cast this as a 'pivot' to Africa, a 'relocation of troops' from Afghanistan and Iraq to the Sahel and Northern Africa. What factors underlie this strategic shift? Despite the importance of this question, to date, little analysis of the decision-making process underpinning the recent change has been forthcoming. The article seeks to address this gap through an analysis of the parliamentary debates on the missions. Specifically, it examines the 'relative importance' of the two threats/challenges motivating the interventions: irregular immigration into the E.U. (and the related smuggling phenomena) and transnational terrorism. The article contributes to the ongoing debate on the evolution of the Italian foreign, security and defence policy in the broader Mediterranean, offering insights for comparative analyses with other states engaged in those contexts.